A Review of Fruit and Vegetable Postharvest Losses in Tanzania - Wanyama, R.; Ernest, Z.; Mvungi, H. (International Food Policy Research Institute, 2022)
This technical report produced by FRESH Initiative Partner Applied Horticultural Research, in collaboration with FRESH Initiative Partner World Vegetable Center, provides an overview of the literature on postharvest losses within fruit and vegetable value chains in Tanzania. The report categorizes the different drivers of postharvest losses, including structural and material barriers faced by farmers and vendors, in addition to known interventions implemented to reduce losses in Tanzania and neighboring countries.